Food & drink : good manufacturing practice : a guide to its responsible management - Manning, Louise (Wiley-Blackwell, 2013)
Good Manufacturing Practice (GMP) refers to advice and guidance put in place to outline the aspects of production and testing that can impact the quality and safety of a product. In the case of food and drink, GMP is aimed at ensuring that products are safe for the consumer and are consistently manufactured to a quality appropriate to their intended use. Manufacturers have for several years been driving towards such goals as Total Quality Management (TQM), lean manufacturing and sustainability - GMP is bound up with these issues. The ever-increasing interest amongst consumers, retailers and.